Nathaniel Cushing papers - Cushing, Nathaniel, 1762-1827.
General correspondence and business and legal papers relating principally to Cushing's business in the manufacture and trade of ships' anchors. Includes material relating to trade with Spain and Portugal.
Manufacturer and merchant of Pembroke, Plymouth County, Mass.
Collection material in English.
Keywords: Anchors; Merchants -- Massachusetts -- Pembroke; Portugal -- Commerce -- United States; Spain -- Commerce -- United States; United States -- Commerce -- Portugal; United States -- Commerce -- Spain; United States -- Commerce -- History; Industrialists; Merchants